Numerical simulation of sudden expansion tubes with Ag-MgO nanofluid and innovative fin structure: A thermo-fluidic analysis - Pazarlıoğlu, Hayati Kadir; Gürsoy, Emrehan; Gürdal, Mehmet; Said, Zafar; Arslan, Kamil; Gedik, Engin (Elsevier BV, 2024)
This study introduces an innovative approach to employing mono/hybrid nanofluids in tubes with sudden expansion, structured at various expansion angles and equipped with novel capsule-type dimpled fins. Pumping of hybrid nanofluids into sudden expansion tube combined with capsule-type dimpled fins and different expansion angles (ranging from 30° to 90°) has not been investigated so far in terms of energy, exergy, and entropy analyses. Recognizing the attention currently devoted to the climate effect of a system exposed to high thermal loads, this study sheds light on the literature how a system preferred by engineers and professionals can be cooled down efficiently to increase the performance of the system. The objective is to analyze a detailed 3E-study (energy, exergy, and entropy production) on water-based mono and hybrid nanofluids, exploring various volume fractions and combinations (including 2.0% Ag, 2.0% MgO, and blends of Ag-MgO). The study finds that a 45° expansion angle, combined with capsule-type dimpled fins and 0.5% Ag-1.5% MgO nanofluid, offers the most efficient tube design, enhancing the average Nusselt number by 20.0%. This configuration, also, reduces total entropy generation by approximately 23.0 % and shows exergy output by 26.0%, though it does lead to a 26.0% decrease in second law efficiency due to increased pumping power. Interestingly, the first law efficiency remains unchanged mainly across different nanofluid types. These findings provide valuable insights into optimizing heat transfer and fluid dynamics in engineering applications.
Keywords: 7. Clean energy